When WAS Gene Diagnosis Is Needed: Seeking Clues Through Comparison Between Patients With Wiskott-Aldrich Syndrome and Idiopathic Thrombocytopenic Purpura - Jin, Ying-Ying; Wu, Jing; Chen, Tong-Xin; Chen, Ji (Frontiers in Immunology, 2019)
Background: Wiskott-Aldrich syndrome (WAS) is a rare and severe X-linked disorder with variable clinical phenotypes correlating with the type of mutations in the WAS gene. The syndrome is difficult to differentiate from idiopathic thrombocytopenic purpura (ITP) before genetic diagnosis. We retrospectively reviewed patients suspected to have WAS who were referred to our hospital from 2004 to 2016 and compared the clinical features and laboratory examination of genetically confirmed WAS patients and of patients diagnosed with ITP in order to seek some clues to distinguish WAS and ITP before genetic diagnosis. Methods: Seventy-eight children suspected to have WAS from 78 unrelated families were enrolled in this study. The clinical data and laboratory examination of children were reviewed in the present study. The distribution of lymphocyte subsets from peripheral blood was examined by ﬂow cytometry. WASP mutations were identified by direct sequencing of PCR-amplified genomic DNA. Results: Forty-two patients were finally diagnosed with WAS genetically. The median onset age of these patients was 1 month (range: 1 day-10 months). The median diagnosis lag was 4.6 months (range: 0 months-9.42 years). Fifteen patients (35.71%) had positive family histories. More than half of the patients (n=23, 54.76%) had diarrhea. Twenty-three (54.76%) had pneumonia, 7 with severe symptoms. Major bleeding events included skin spots or petechiae (n=27, 64.29%), per-rectal bleeding (n=21, 50.00%), epistaxis (n=7, 16.67%) and intracranial bleeding (n=2, 4.76%). Twenty-nine patients (69.05%) had eczema, and one patient had a drug allergy. Three patients had autoimmune diseases, among whom 2 had autoimmune hemolytic anemia and one had autoimmune hemolytic anemia and IgA nephropathy. A total of 42 mutations in WASP were identified, including 19 novel mutations. Eight patients received HSCT and all survived. Compared with the 30 patients diagnosed with ITP, the WAS patients had higher EOS counts and elevated IgE level, increased NK cell numbers but fewer CD8+T lymphocytes. Conclusion: The WAS gene diagnosis should be considered in all males with ITP-like features, especially for patients with a very early onset age, decreased MPV (<6.5 fl), higher EOS counts and elevated IgE level, increased NK cell number, diminished CD8+T lymphocyte count.